TAX REFORMS AND GROSS DOMESTIC PRODUCT OF NIGERIA (Journal of Global Accounting, 2024)
This study ascertained the effect of tax reforms on gross domestic product of Nigeria for eighteen years ranging from 2005-2022. Specifically, this study ascertained the effect of changes in Personal Income Tax Revenue, Company Income Tax Revenue, and Petroleum Profit Tax Revenue on Gross Domestic Product. The time series data sets used in this study were obtained from Central Bank of Nigeria Statistical Bulletin, Securities and Exchange Commission Office publications, National Bureau of Statistics publications and World Bank Statistical Bulletin for the study period. Ex-post facto research design was employed. Inferential statistics using Augmented Dickey-Fuller (ADF) test, Pearson correlation coefficient, and Ordinary Least Square regression analysis were applied to test the hypotheses of the study. The specific findings showed that Personal Income Tax has a significant but negative effect on Gross Domestic Product of Nigeria (β1 = -0.582688; p-value = 0.0020
Keywords: Company Income Tax; Gross Domestic Product; Personal Income Tax; Petroleum Profit Tax